Autoimmune Polyglandular Syndrome Type 2 and Pregnancy - Vesselina Yanachkova (Folia Medica, 2020)
Autoimmune polyglandular syndromes are combinations of various endocrine and nonendocrine autoimmune diseases, as well as the presence of elevated organ-specific antibody titers. We present a clinical case of a 41-year-old pregnant patient with type 2 autoimmune polyglandular syndrome, combining Addison’s disease, Hashimoto’s thyroiditis and hypogonadism. The pregnancy was achieved after the use of assisted reproductive technology. During the pregnancy the patient was strictly monitored. Glucocorticoid and mineralocorticoid replacement therapy was adjusted according to the electrolyte profile and general condition of the patient. Management during pregnancy was difficult due to fluctuations in electrolyte levels, thyroid hormones and orthostatic manifestations. Prior to delivery adrenal crisis occurred, but the condition was successfully managed. No complications were reported for the mother and the newborn.